2020
DOI: 10.3389/fpls.2020.01212
|View full text |Cite
|
Sign up to set email alerts
|

Species Identity and Initial Size Rather Than Neighborhood Interactions Influence Survival in a Response-Surface Examination of Competition

Abstract: To measure intraspecific and interspecific interaction coefficients among tree species is the key to explore the underlying mechanisms for species coexistence and biodiversity maintenance in forests. Through the response surface experimental design, we established a long-term field experiment by planting 27,300 seedlings of four tree species (Erythrophleum fordii, Pinus massoniana, Castanopsis fissa, and Castanopsis carlesii) in 504 plots in different species combinations (six pairwise combinations of four spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
2
2
1
Order By: Relevance
“…However, both factors explained only a tiny fraction of the variation in survival relative to the amount explained by species identity alone. This contrasts with other studies of tree survival that have found that site conditions like slope, elevation, distance to forest edge, and soil conditions impact survival (Shen et al 2020;Wang et al 2022). However, the variation in elevation (from 5 to 25 m) at our site is much smaller than in previous studies with a significant elevation effect.…”
Section: Limited Impact Of Abiotic Factors and Deer Browse On Survivalcontrasting
confidence: 98%
See 2 more Smart Citations
“…However, both factors explained only a tiny fraction of the variation in survival relative to the amount explained by species identity alone. This contrasts with other studies of tree survival that have found that site conditions like slope, elevation, distance to forest edge, and soil conditions impact survival (Shen et al 2020;Wang et al 2022). However, the variation in elevation (from 5 to 25 m) at our site is much smaller than in previous studies with a significant elevation effect.…”
Section: Limited Impact Of Abiotic Factors and Deer Browse On Survivalcontrasting
confidence: 98%
“…Instead, species identity was the variable that explained most variation in survival across all models, similar to other tree diversity experiments (Potvin & Gotelli 2008;Philipson et al 2014;Shen et al 2020). The substantial range in mortality rates among individual species in our study adds to the body of evidence that individual characteristics are more important determinants of sapling survival than neighborhood diversity (Philipson et al 2014;Shen et al 2020). Our study also went beyond some previous work to evaluate functional and phylogenetic diversity impacts on survival, but we still found no evidence that diversity impacts survival.…”
Section: Species Identity Rather Than Diversity Metrics Explain Most ...supporting
confidence: 77%
See 1 more Smart Citation
“…Pretzsch et al, 2015; Sapijanskas et al, 2013; Van de Peer et al, 2018). Beyond species richness, species functional composition influenced the survival and growth of communities (Fig S1, Fig S2) (Potvin & Gotelli, 2008; Salisbury & Potvin, 2015; Shen et al, 2020; Yang et al, 2013). However, despite considerable differences in growth rates among experimental species, inclusion of fast-growing species alone did not explain the observed increase in biomass in high-diversity treatments (Fig 3).…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic properties of the seedling, such as species identity and initial seedling size, may be the key factors in determining the seedling survival rate in the field (Shen et al, 2020). Gardiner et al (2019), indicates that planting seedlings between 25 and 35 cm tall will increase the early survival and growth rate of the seedlings in restoration projects in degraded areas.…”
Section: Tree Seedling Quality and Factors Affecting Its Quality Prod...mentioning
confidence: 99%